Uncovering Potential Health Beneficial Nutrient of Underutilized Crop Waste: An Insight from Ash and Metal Content Study of Banana Corm - Indradi, Raden Bayu; Tjitraresmi, Ami; Ramadhania, Zelika Mega; Diwest, Dani Jermi (Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, 2024)
Banana corm is considered unvaluable agricultural waste and is mainly discarded and left unused once the fruits are harvested. Uncovering the hidden values of this waste could be beneficial because of its abundance as a source. Hence, here we study the metal content of banana corm to find its potential health nutrients. The corm from three banana species, Musa balbisiana Colla., Musa x paradisiaca L. AAA, and Musa x paradisiaca L. ABB were collected, prepared, dried, and extracted with ethanol 70%. Dried material and extracts obtained were subjected to total ash and acid insoluble ash determination by gravimetric method and further subjected to metal determination by ICP-EOS tools. The results showed that M. x paradisiaca AAA showed the highest ash content among all three banana species in dried materials and extracts with values of 7.64% and 31.06%, respectively. The most abundant metal contained is potassium, with a M. x paradisiaca AAA had the highest content of potassium in dried samples with 18.774%. It is concluded that banana corm could be a potential source of potassium, which is beneficial in dietary or as supplementation to increase the daily intake of potassium to improve general health.